СҮТ ӨНІМНІҢ САПАСЫН ЖƏНЕ ҚАУІПСІЗДІГІН ЖЕТІЛДІРУДІҢ НЕГІЗГІ ШАРАЛАРЫ (Experimental biology, 2015)
For definition of the general quantity of microorganisms of a cattle-breeding complex the analysis of soil, water, a forage, milk is carried out. For the purpose of improvement of quality of milk we spend all complex of the researches influencing its safety.
Keywords: analysis of soil; analysis of water; analysis of a forage; analysis of milk